In vivo evaluation of microencapsulated bicistronic plasmid DNA vaccine against Vibrio cholerae - Ahmad Zamri, Najwa (2021)
The aggression of cholera infection in some parts of the world is seen as one of the major public health concerns in global perspective due to its epidemic and pandemic potentials. As an approach to control the outbreak in risky regions and endemic areas, oral cholera vaccines (OCVs) which utilise conventional vaccinology strategy using killed whole-cell Vibrio cholerae have been recommended as a preventive measure. However, they possess several drawbacks in terms of vaccine handling and storage, logistics and cost values besides their safety concerns in high-risk individuals. As an alternative over the conventional OCVs, the concept of bicistronic DNA vaccine encoding immunostimulatory antigens which are cholera toxin subunit B (ctxB) and toxin coregulated pilus subunit A (tcpA) genes from V. cholerae was explored in this study. A previous study has demonstrated the potential role of bicistronic vaccine construct in vitro through its successful expression in COS-7 cells. However, evaluation on immunogenicity of the vaccine has not been conducted in vivo. Therefore, the main objective of this study was to evaluate the in vivo potential of the microencapsulated bicistronic plasmid DNA (pDNA) vaccine against cholera infection using removable intestinal tie adult rabbit diarrhea (RITARD) model. For a successful delivery through oral route, encapsulation of the vaccine using alginate microspheres was developed through water-in-oil emulsification with encapsulation efficiency of 88.6% and further validated through physical and behavioural characterisations of the microspheres. Successful pDNA delivery was also observed using a simulated gastrointestinal pH condition. Subsequently, oral vaccination with these alginate-encapsulated-vaccines was performed in vivo using seven-week-old New Zealand White (NZW) rabbits. Fifteen female rabbits were used in this study and divided into five groups: (1) Mock-infected control (negative control); (2) Empty alginate microsphere (non-vaccinated); Alginate microspheres encapsulating (3) pVAX-ctxB; (4) pVAX-tcpA; and (5) pVAX-ctxB-tcpA. Except for group 1, other test groups were challenged with V. cholerae of serotype Ogawa and biogroup El Tor, two weeks after the vaccination, by utilising the RITARD model. The animals were monitored for cholera symptoms five days’ post-surgery and rectal swab cultures for V. cholerae of Group 5 (bicistronic vaccine construct) showed negative results. On the other hand, cholera infection was not evident in the bicistronic vaccine group based on gross examination in post-mortem and histological analyses. Besides that, the cytokine expression level (TNF-α, IFN-γ, IL-10 and IL-6) was evaluated using quantitative polymerase chain reaction (qPCR) following the immunisation and infection challenge. The bicistronic group showed an increase of systemic IFN-γ and IL-10 at 12-day post-vaccination, though not significant, indicating the possible activation of both T-helper 1 and 2 types of response. However, the level of all cytokines did not change after the infection challenge. In brief, the alginate encapsulating bicistronic pVAX-ctxB-tcpA portrays a potential in inducing host immune response against cholera infection, although several improvements and comprehensive analyses are required to evaluate its role as a DNA vaccine.